1950
DOI: 10.1111/j.1399-3054.1950.tb07490.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α‐Naphthaleneacetic Acid on Dichotomous Branching of Isolated Roots of Pinus silvestris (A Preliminary Report)

Abstract: As has been shown in an earlier paper (Slankis 1948). dichotomous branching may be produced in isolated pine roots by addition of exndates of mycorrhi/al fungi (e.g. species of Boletus) to tbe nutritive solution. Similar branching of pine roots occurs in nature, according to the investigations of Melin (1923) and others, in connection witb the formation of mycorrhiza. Further investigations (Slankis 1949) indicated tbat ^-indoleacetic acid might be one of the components of the fungous exudates which cause this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

1965
1965
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 5 publications
2
13
0
1
Order By: Relevance
“…Not all mycorrhizal fungi produce auxins, and several nonmycorrhizal species associated with the roots of forest trees do produce auxin. Moreover, auxins induce the proliferation of lateral roots, a phenomenon that is not characteristic of ectomycorrhizas (Slankis, 1950(Slankis, , 1973Wilson & Field, 1984 ;Torrey, 1986). Sensitive measurements of IAA in roots indicated that levels were generally lower in mycorrhizal roots than in control roots Lomax et al, 1995), and a study comparing the response of pine roots to fungal strains producing different amounts of auxin found no relationship between auxin production and root morphology .…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations
“…Not all mycorrhizal fungi produce auxins, and several nonmycorrhizal species associated with the roots of forest trees do produce auxin. Moreover, auxins induce the proliferation of lateral roots, a phenomenon that is not characteristic of ectomycorrhizas (Slankis, 1950(Slankis, , 1973Wilson & Field, 1984 ;Torrey, 1986). Sensitive measurements of IAA in roots indicated that levels were generally lower in mycorrhizal roots than in control roots Lomax et al, 1995), and a study comparing the response of pine roots to fungal strains producing different amounts of auxin found no relationship between auxin production and root morphology .…”
Section: mentioning
confidence: 99%
“…αNAA induces lateral root formation Slankis (1950) reported that treatment of P. sylvestris root cultures with the synthetic auxin αNAA, at concentrations of c. 8-13 µM, induced extensive lateral root formation and dichotomous branching of some of these lateral roots. We confirmed that treatment of axenic root cultures of P. sylvestris with 10 µM αNAA induced profile lateral root formation within 4 wk (Fig.…”
Section: Lateral Root Morphogenesis In Cultured Pine Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slankis (1950Slankis ( , 1973) applied exogenous IAA, or culture filtrates of two ectomycorrhizal fungi, Suillus luteus and Suillus variegatus, to excised Pinus sylvestris roots. He observed a stimulation of root branching and formation of dichotomous lateral roots, lacking root hairs and morphologically similar to ectomycorrhizas.…”
mentioning
confidence: 99%
“…Work is beiag conducted upon mycorrhizal fungi that are antagonistic to other soil organisms (Manka, 1960;Santoro and Casida, 1962); and upon the production of auxins by mycorrhizal fungi along with the effect of these auxins upon the morphology of the root system (Slankis, 1950(Slankis, , 1960Ulrich, 1960aUlrich, , 1960b)« Recently a new classification scheme for ectotrophic mycorrhizae has been devised based upon morphological and anatomical characteristics (Dominik, 1959).…”
Section: Literature Reviewmentioning
confidence: 99%